Preventive Maintenance Supply Chain Management Optimal Scheduling on VMACL Machines by Implementing Simulation Annealing Algorithms - Yuyun Hidayat; Titi Purwandari; Achmad Bachrudin; Aziza Ayu Nurjannah; Agus Santoso; Sukono Sukono (International Journal of Supply Chain Management, 2020)
PT. Braja Mukti Cakra uses various types of engines to produce parts for truck cars. Vertical Lathe Automatic Chucking Machine (VMACL) is a machine that has the highest frequency of damage when compared to other machines. To reduce damage costs, preventive maintenance is well scheduled. This scheduling problem solving is done using the Annealing Simulation Algorithm. The results of the analysis give direction that the scheduling that must be done are: The maintenance action schedule for the Lifter component is at month 1,6,7,22,24,34, for the Insert component at 4,15,18,27,33 months, and for the Door component at the 2nd month, 12,13,16,17,30,36. Replacement actions for the Lifter component were carried out in the 4,5th month, 1,17,20,29, for the Insert component in the 9,19,22,23,35 months, and for the Door component in the 1,20,27 months. . Scheduling for 36 months using the Simulated Annealing Algorithm will cost IDR. 84,119,244.60 and produce greater reliability than the previous reliability of 58.44%.